General Criticism of Modern-Contemporary Western Rationality. Geopolitics of Knowledge I - Guendel Angulo, Hermann (2025)
This essay contains an interpretation of the origin of modern Western rationality and, therefore, of its consequences we still grapple with today. It also considersits functioning in modernity and contemporaneity, proposing a hypothesis on the scope and impact of the changes in the predominant rationality observed in the current new post-contemporary era.